1997
DOI: 10.1038/sj.hdy.6881500
|View full text |Cite
|
Sign up to set email alerts
|

Fitness compensation and the evolution of selfish cytoplasmic elements

Abstract: Cytoplasmic incompatibility (CI) and male-killing (MK) are both examples of the action of selfish cytoplasmic elements. Both are found in a wide variety of host arthropod species and sometimes coexist within the same species. Although classical models suggest that fitness compensation is potentially important in explaining the invasion of the MK cytotype, no mode! of CI evolution incorporates this effect. We construct a discrete-time mathematical model which describes a host population containing both CI and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
0
6
1
Order By: Relevance
“…In previous models (Hurst 1991;Hurst et al 1997;Freeland & McCabe 1997;Randerson et al 2000) region III has not been observed, because, in contrast to our model, the number of males was never limiting and the total population size was always xed, i.e. all fractions always added up to 1.…”
Section: (C) High Transmission Ef Cienciescontrasting
confidence: 67%
See 1 more Smart Citation
“…In previous models (Hurst 1991;Hurst et al 1997;Freeland & McCabe 1997;Randerson et al 2000) region III has not been observed, because, in contrast to our model, the number of males was never limiting and the total population size was always xed, i.e. all fractions always added up to 1.…”
Section: (C) High Transmission Ef Cienciescontrasting
confidence: 67%
“…Previously, a number of mathematical models have been developed to describe a host population with malekilling bacteria in terms of vertical transmission ef ciency, and positive and negative effects of infection (Hurst 1991;Hurst et al 1997;Freeland & McCabe 1997;Randerson et al 2000). Using a discrete generation model, Hurst (1991) showed that invasion of a male killer is only possible when both the vertical transmission is imperfect (described by a , 1) and there is a positive effect on the tness of the female host of carrying the infection.…”
Section: Introductionmentioning
confidence: 99%
“…To date, only one of the published models on CI incorporates such a mechanism. Freeland and McCabe (1997) have shown that a CI element can invade an uninfected population by hitchhiking with a male-killing (MK) element. In essence, the fitness cost of the CI element is compensated with a fitness benefit of the MK element.…”
Section: How To Overcome the Invasion Threshold?mentioning
confidence: 99%
“…In addition, the vertical transmission efficiency of different male-killing bacteria varies from almost perfect (> 99% for Spiroplasmas in A. bipunctata and H. axyridis and one strain of Wolbachia in A. bipunctata ) to less than 72% for Rickettsia in some samples of A. bipunctata [ 16 - 18 ]. The vertical transmission efficiency is a critical parameter in the dynamics of male-killer invasion and spread [ 19 ]. Assessments of the vertical transmission efficiencies of newly discovered male-killers are thus valuable to allow assessment of whether levels of vertical transmission are consistent within bacterial clades, or vary case by case as a result of interactions between each symbiont and its host.…”
Section: Introductionmentioning
confidence: 99%